A national examination of pharmacy-based immunization statutes and their association with influenza vaccinations and preventive health. Issue 30 (24th June 2016) - McConeghy, Kevin W.; Wing, Coady
Highlights: From 1996 to 2010, 41 states changed statutes to allow pharmacists to immunize. Per capita influenza vaccine prescriptions increased by 2.6 percentage points after state adoption. However, this did not lead to significantly increased adult vaccination rates. Abstract: Background: A series of state-level statute changes have allowed pharmacists to provide influenza vaccinations in community pharmacies. The study aim was to estimate the effects of pharmacy-based immunization statutes changes on per capita influenza vaccine prescriptions, adult vaccination rates, and the utilization of other preventive health services. Methods: A quasi-experimental study that compares vaccination outcomes over time before and after states allowed pharmacy-based immunization. Measures of per capita pharmacy prescriptions for influenza vaccines in each state came from a proprietary pharmacy prescription database. Data on adult vaccination rates and preventive health utilization were studied using multiple waves of the Behavioral Risk Factor Surveillance System (BRFSS). The primary outcomes were changes in per capita influenza vaccine pharmacy prescriptions, adult vaccination rates, and preventive health interventions following changes. Results: Between 2007 and 2013, the number of influenza vaccinations dispensed in community pharmacies increased from 3.2 to 20.9 million. After one year, adopting pharmacist immunization statutes increased per capita influenza vaccine prescriptions by an absolute difference (AD) of 2.6% (95% CI: 1.1–4.2). Adopting statutes did not lead to a significant absolute increase in adult vaccination rates (AD 0.9%, 95% CI: −0.3, 2.2). There also was no observed difference in adult vaccination rates among adults at high-risk of influenza complications (AD 0.8%, 95% CI: −0.2, 1.8) or among standard demographic subgroups. There also was no observed difference in the receipt of preventive health services, including routine physician office visits (AD −1.9%, 95% CI: −4.9, 1.1). Conclusions: Pharmacists are providing millions of influenza vaccines as a consequence of immunization statutes, but we do not observe significant differences in adult influenza vaccination rates. The main gains from pharmacy-based immunization may be in providing a more convenient way to obtain an important health service.